Wearing a head-mounted eye tracker may reduce body sway - Gotardi, Gisele C. [UNESP]; Rodrigues, Sérgio T. [UNESP]; Barbieri, Fabio A. [UNESP]; Brito, Matheus B. [UNESP]; Bonfim, José V.A. [UNESP]; Polastri, Paula F. [UNESP] (Elsevier, 2020)
This study investigated the effects of wearing a head-mounted eye tracker on upright balance during different visual tasks. Twenty five young adults stood upright on a force plate while performing the visual tasks of fixation, horizontal saccades, and eyes closed, during eighteen trials wearing or not a head-mounted eye tracker. While wearing the eye tracker, participants showed a reduction in mean sway amplitude and velocity of the CoP in the AP and ML directions and more regular CoP fluctuations, in the ML axis in all conditions. Higher mean sway amplitude and velocity of CoP were observed during eyes closed than fixation and saccades. Moreover, horizontal saccades reduced mean sway velocity of CoP compared to fixation. Therefore, wearing the eye tracker minimized the body sway of young adults; however, visual task-related effects on postural stability remained unchanged.
Keywords: Gaze fixation; Head stabilization; Head-mounted eye tracker; Postural control; Saccadic eye movements